Dysregulated Innate and Adaptive Immune Responses Discriminate Disease Severity in COVID-19. (1st February 2021) - Janssen, Nico A F; Grondman, Inge; de Nooijer, Aline H; Boahen, Collins K; Koeken, Valerie A C M; Matzaraki, Vasiliki; Kumar, Vinod; He, Xuehui; Kox, Matthijs; Koenen, Hans J P M; Smeets, Ruben L; Joosten, Irma; et al.
Abstract: The clinical spectrum of COVID-19 varies and the differences in host response characterizing this variation have not been fully elucidated. COVID-19 disease severity correlates with an excessive proinflammatory immune response and profound lymphopenia. Inflammatory responses according to disease severity were explored by plasma cytokine measurements and proteomics analysis in 147 COVID-19 patients. Furthermore, peripheral blood mononuclear cell cytokine production assays and whole blood flow cytometry were performed. Results confirm a hyperinflammatory innate immune state, while highlighting hepatocyte growth factor and stem cell factor as potential biomarkers for disease severity. Clustering analysis revealed no specific inflammatory endotypes in COVID-19 patients. Functional assays revealed abrogated adaptive cytokine production (interferon-γ, interleukin-17, and interleukin-22) and prominent T-cell exhaustion in critically ill patients, whereas innate immune responses were intact or hyperresponsive. Collectively, this extensive analysis provides a comprehensive insight into the pathobiology of severe to critical COVID-19 and highlights potential biomarkers of disease severity. Abstract : Increasing COVID-19 disease severity is characterized by higher circulating levels of inflammatory markers, differential expression of HGF (higher) and SCF (lower), a hyperinflammatory innate immune system, and a severely dysfunctional adaptive immune system.